The Effects Of Heat-Moisture Treatment On The Physicochemical Properties Of Sago (Metroxylon Sagu) Starch [TP416.S3 P743 2006 f rb]. - Poe, Yi Shin (2006)

(untitled)
Kesan pengolahan haba-lembapan terhadap sifat-sifat fizikokimia kanji sagu telah dilakukan pada kandungan lembapan 13%, 18% dan 30%.